Assessing the effects of coral reef habitat and marine protected areas on threatened megafauna using aerial surveys. Issue 3 (12th February 2023) - Heudier, Mickael; Mouillot, David; Mannocci, Laura
Abstract: Overfishing and habitat degradation are major threats to marine megafauna worldwide. Marine protected areas (MPAs) are effective spatial conservation tools for reducing anthropogenic pressures on threatened species but their benefits for megafauna are still debated. While the effects of MPAs on species abundances are widely reported, few studies have simultaneously investigated the confounding effect of habitat. This study aimed at disentangling the effects of coral reef habitat and spatial protection on megafauna densities in a shallow lagoon partly covered by a no‐take MPA in New Caledonia (South‐west Pacific). Twenty replicates of aerial‐video surveys (representing 17 h of videos) were conducted during a 5‐month period to estimate and map the densities of five megafauna taxa (dugongs, sea turtles, sharks, Dasyatidae rays and Myliobatidae rays). A permutational multivariate analysis of variance was then applied to assess and disentangle the effects of coral reef habitat obtained from high‐resolution satellite imagery and spatial protection on megafauna taxa densities. The analysis revealed a significant effect of protection for sharks and Myliobatidae, with observed densities respectively 9 and 3 times higher inside the MPA compared with outside. The results also highlighted a significant combined effect of habitat and protection for dugongs and Dasyatidae, as well as a significant effect of habitat alone for Dasyatidae. In contrast, no significant effect of habitat or protection was detected for sea turtles. In conclusion, this study revealed positive effects of protection (alone or combined with habitat) for four of the five studied megafauna taxa, confirming the effectiveness of the current MPA. Future studies should be conducted over broader spatial and temporal scales to examine whether detected effects hold beyond the surveyed period and area.